IMPLEMENTASI PROGRAM INDONESIA PINTAR (PIP) DI SMA KECAMATAN BANYUMANIK KOTA SEMARANG - Musyaffa Marsa, Devin; Santoso, R. Slamet (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
The Smart Indonesia Program (PIP) is a government program in the education sector in an effort to overcome school dropouts in Indonesia. Students at the high school level in Banyumanik District who received PIP Assistance amounted to 316 students. This study uses a qualitative method with a purposive sampling technique. Data sources are from the results of interviews, observations and documentation. This study aims to determine the policy implementation process and identify factors that affect the implementation of the Smart Indonesia Program in Banyumanik District by combining Riant Nugroho's theory of Accuracy with Mazmanian/Sabatier Policy Implementation. The results of the study show that the implementation of PIP in Banyumanik District has not gone well, marked by the fact that there are still many parents of students who do not understand the mechanism of PIP distribution, so that students who experience delays in activating PIP disbursement fund accounts are hampered and cause the recipient quota to be reduced. Influencing factors include the characteristics of the problem, political support and implementation stages, it was also found that party interest factors affect the running of PIP, where the requirements for the candidacy of PIP recipients proposed by political parties are different from regulations regarding PIP so that the disbursement of PIP funds is not on target. The recommendation in the study is to conduct more intense socialization related to PIP monitoring and evaluation to ensure that recipient data is valid and on target, so that it is in accordance with applicable regulations.